The Statistical Study Of Malocclusions - Georgeta Zegan; Daniela Anistoroaiei (Romanian Society of Oral Rehabilitation, 2009)
The aim of this study is to achieve a statistical evaluation on a consignment of patients who have addressed the Dental ambulatory for children (Iaşi) for orthodontic consulting over a period of 10 years (1990 - 2000). The study has been performed on 375 patients (157 boys and 218 girls) aged between 4-24 years, with malocclusions. The diagnosis was established by clinical and paraclinical exams (cast and radiological measurements). Both removable and fixed appliances were used in conducting the treatment. The data base was created with MS Excel and the statistical evaluation was completed with the SPSS-15 and the EPI-Info-15 software, using descriptive statistics, bivalent correlations and linear regression. The Patients in need of orthodontic treatment presented malocclusion Class I 63,2%, Class II 28,3%, and Class III 5,8%. The group and isolated malocclusion proportion varied on the basis of the clinical manifestations asociated to the malocclusion Class. Based on age, the patients were applied with prophylactic treatment 3%, interceptive treatment 5% and curative 92%. The Pearson corelations made on the consigment of patients prooved the existence of a directly proportional link between the therapeutical results, the diagnosis of the malocclusions and the treatment chosen to be carried out. The Fisher test applied on the ortodontic treatment, the diagnosis Class and the therapeutical results proved to be significant in the statistics. The results of the prevalence maloclusion types are comparable with the ones from the speciality literature. The corelations that were carried out were based on medical reasoning. The regression model of prediction is probabilistic.